1999
DOI: 10.1007/bf03161735
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying impacts to riparian wetlands associated with reduced flows along the Greybull River, Wyoming

Abstract: Reductions in river flows associated with hydrologic changes from diversions may reduce water elevations and impact hydrology of riparian wetlands. The U.S, Army Corps of Engineers and other federal agencies currently do not have appropriate tools to evaluate effects of hydrologic changes on wetlands. We describe use of ttEC-RAS modeling to predict and quantify wetland impacts along 10 kin of the Greybull River, Wyoming, USA following a proposed 28,313 L/see diversion for a new off-channel reservoir. Riparian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Biohydrology studies have examined relationships of riparian vegetation with many hydrologic parameters including seasonal or annual stream flow rate, magnitude and variability of base flows, depth to ground water or saturated soil, and frequency, timing and magnitude of flood pulses (Nestler and Long, 1997;Friedman and Auble, 1999;Johnson, 2000;Pettit et al, 2001;Elmore et al, 2003). Vegetation can be characterized in many ways, and studies have examined effects of surface-and ground-water flow regimes on vegetation abundance, plant species diversity, species composition, establishment and survival of tree species, and plant growth and vigour (Stromberg andPatten, 1990, 1995;Smith et al, 1991;Shafroth et al, 1998Shafroth et al, , 2000Shafroth et al, , 2002Johnson et al, 1999;Scott et al 1999;Munoz-Reinoso, 2001;Capon, 2003;Cooper et al, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Biohydrology studies have examined relationships of riparian vegetation with many hydrologic parameters including seasonal or annual stream flow rate, magnitude and variability of base flows, depth to ground water or saturated soil, and frequency, timing and magnitude of flood pulses (Nestler and Long, 1997;Friedman and Auble, 1999;Johnson, 2000;Pettit et al, 2001;Elmore et al, 2003). Vegetation can be characterized in many ways, and studies have examined effects of surface-and ground-water flow regimes on vegetation abundance, plant species diversity, species composition, establishment and survival of tree species, and plant growth and vigour (Stromberg andPatten, 1990, 1995;Smith et al, 1991;Shafroth et al, 1998Shafroth et al, , 2000Shafroth et al, , 2002Johnson et al, 1999;Scott et al 1999;Munoz-Reinoso, 2001;Capon, 2003;Cooper et al, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Hydrologic models of various complexities have been developed and applied to a number of wetland studies focusing on hydrology (Sun et al 1998;Pyke 2004;Boone et al 2006), wetland hydrology and vegetation relations (Poiani and Johnson 1993), and the specific effects of streamflow alteration on wetland systems (Johnson et al 1999;Auble et al 2005). This study demonstrated that the SPAW model is a suitable tool for use in the simulation of the hydrology of bottomland forest wetlands of the Midwest U.S. that are dominated by surface-water processes.…”
Section: Wetland Hydrology Characteristicsmentioning
confidence: 99%
“…Wetland ecosystems in arid and mesic regions throughout the world are being affected by hydrologic alterations including ground-water pumping and stream flow diversion (Rood et al, 1995;Johnson et al, 1999;Kingsford, 2000;MunozReinoso, 2001;Elmore et al, 2003;Tockner and Stanford, 2002). In southwestern USA, the Colorado River and many of its tributaries have been partially or wholly dewatered as water is appropriated for urban, agricultural and industrial use (Judd et al, 1971;Medina, 1990;Springer et al, 1999;Glenn et al, 2001;Stromberg et al, 2004a).…”
Section: Introductionmentioning
confidence: 97%